Shared parenting in Malaysia and Australia: an overview - Ali, Suzana; Che Soh @ Yusoff, Roslina (2015)
Issue on ‘welfare of the child’ has been highlighted in many international conventions, charters and others. Thus, shared parenting has also been agreed to be the best method in protecting welfare of the child. Whereas, in Islamic law, though there is no specific provision on shared parenting, it is well understood that both parents should have good agreement in matters relating to their children. In Malaysia, the legislations on child custody emphasize that welfare of the child shall be the paramount consideration but they do not have any provisions on shared parenting and specific guidelines on its implementation and application. Amendment was made to the laws to include a provision of equal parental rights but it does not directly relate to the principle of shared parenting. The vagueness of the laws and the absence of the proper guidelines in relation to shared parenting open the doors for the courts to have inconsistent decisions in determining custodial rights and often decide in favour of sole custody. The absence of specific laws on shared parenting has also caused difficulties for the parents to cooperate for the sake of the children. They always stress on their conflicts and fighting for their rights rather than to focus on the welfare of the children. This paper seeks to discuss the current position of shared parenting after marital separation in Malaysia. As Malaysia practises dual legal systems, this paper will examine the suitability of the shared parenting principle to be applied in both systems. A brief comparative review will also be made to Australia which is more develop in the laws and policies on shared parenting. Finally, the paper will provide comments and suggestions to improve the currents law in Malaysia. Doctrinal methodology is used in this paper in arriving at the findings of the work.